GlobaLIS : an effort to describe trends in Japanese LIS education for global collaboration / Makiko Miwa, Yumiko Kasai and Shizuko Miyahara - Miwa, Makiko; Kasai, Yumiko; Miyahara, Shizuko (2011)
The GlobaLIS Project takes an initiative in attaining the globalization of Japanese library and information science (LIS) professional education by defining the requirements for internationally transparent and harmonized educational programs for LIS professionals. We ask three research questions in a stepwise manner: (1) What are the basic requirements for globalizing Japanese LIS professional education? (2) What kinds of efforts are required for us to attain a global collaboration between Asia and the Pacific in quality assurance of LIS education? (3) How can we attain global collaboration in the development of a common curriculum framework for LIS education in Asia and the Pacific using school librarian training as an instantiation? At the initial stage of the GlobaLIS project, we reviewed the literature and interviewed people involved in regional and global collaboration for quality assurance and mutual accreditation of LIS educational programs, to identify the recent trends. For the first research question, we identified three requirements: (1) establishment of an office responsible for preparing and administering mutual accreditation of LIS programs with overseas counterparts,(2) implementation of the LIS examination as a means of establishing an outcome-based assessment of LIS education, and(3) establishment of graduate level LIS education programs to be mutually exchangeable with overseas counterparts. For the second research question, we tentatively identified three areas requiring effort: (1) improvement of international transparency of the Japanese LIS professional system,(2) comparison of the LIS curriculum contents with those of overseas counterparts, and(3) stimulation of interest in global trends in LIS education among Japanese LIS educators. For the third research question, we have begun preparation for the collaborative curriculum development of school library professionals planned for 2013. Keywords: Library and Information Science (LIS) education; Global collaboration; Mutual accreditation; Common curriculum development; School library professionals; Comparative librarianship